2013
DOI: 10.4314/ejesm.v6i2.10
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Transportation Facilities Effects on Agricultural Development in Moro Local Government Area, Kwara State, Nigeria

Abstract: This paper was designed to assess the state and effects of transportation facilities on agricultural development of rural farmers in Moro Local Government Areas of Kwara State. The study made use of structured interview schedules to collect data from 150 farmers by means of four-stage random sampling technique. Analytical tools used include Pearson Product moment correlation and Kruskalwallis ranking. Findings show that mode of transportation in the study area is mostly through headporterage and to a short dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…There is a basic consensus in relevant studies that transport infrastructure facilitates the development of regional economies and industries [41,42], and for the development of agriculture and rural industries, the driving role of transportation infrastructure remains [43]. Existing studies have provided evidence from Africa [44,45], Australia [46], and the Americas [47]. Using data from China, this study confirms the role of transportation infrastructure as a driver of rural industrial integration.…”
Section: The Impact Of Transport Infrastructure On the Quality Of Rur...supporting
confidence: 64%
“…There is a basic consensus in relevant studies that transport infrastructure facilitates the development of regional economies and industries [41,42], and for the development of agriculture and rural industries, the driving role of transportation infrastructure remains [43]. Existing studies have provided evidence from Africa [44,45], Australia [46], and the Americas [47]. Using data from China, this study confirms the role of transportation infrastructure as a driver of rural industrial integration.…”
Section: The Impact Of Transport Infrastructure On the Quality Of Rur...supporting
confidence: 64%
“…In a related study, Akangbe et al (2013), Lawal et al (2016), Yeboah (2016 and Claudia (2017) found that high transportation costs would discourage farmers from participating in local markets from selling their livestock and other farm produce, focusing instead on farm gate sales, which would limit their incomegenerating opportunities.…”
Section: Hypotheses Testingmentioning
confidence: 99%
“…However, transportation is indispensable to economic development especially in a developing country like Nigeria. This is because transport is essential in the execution of daily economic and social activities in any given area (Akangbe, Oloruntoba, Achem and Komolafe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that rural areas are characterized by increased agricultural activities. Akangbe et al (2013) explained that agriculture is the primary and biggest source of income in rural communities and provides employment to approximately 70 percent of its population. Hill (2008) opined that a significant proportion of agricultural task involves moving equipment and materials from one place to another in a wide variety of types and sizes of loads to be moved over different distances and types of terrain.…”
Section: Introductionmentioning
confidence: 99%